Usefulness of Urinary Creatinine/Urea Nitrogen Ratio as Indicator of Body Protein Catabolism in Dogs Fed Low Protein Diets - Yamamoto, Shushi; Ohta, Yoshiyuki; Hasegawa, Etsuko; Hashida, Shiori; Kaneko, Yasuyuki; Mizutani, Shinya; Ong, Benedict Huai Ern; Naganobu, Kiyokazu; Torisu, Shidow (Frontiers in Veterinary Science, 2019)
Low protein diets (LPs) constitute a reportedly effective form of nutritional therapy for canine chronic kidney disease and cirrhosis. These diets have long been feared to result in reduced muscle mass due to protein catabolism. This adverse effect, however, remains largely unrecognized in veterinary medicine as there are no easily applicable catabolism indicators. Therefore, we focused on urinary creatinine, a metabolite of protein in the urine, and examined whether its ratio to urinary urea nitrogen (UCrn/UN) can be used to assess protein catabolism. In Experiment 1, we first consecutively fed seven healthy beagles an LP, standard protein (SP), and high protein (HP) diet for 1 week each and then measured the UCrn/UN ratio at 2-h intervals from fasting to 16 h post-prandially. We consequently found that the UCrn/UN ratio was significantly elevated in the LP pre-prandially and at all post-prandial measurement points (P < 0.01). No significant differences were observed between the SP and HP. Analysis of fasting plasma amino-acid concentrations revealed that the concentration of methionine was significantly lower in the LP than in the other diets (P < 0.05). Although the effects of this change in amino-acid concentration were unclear, the UCrn/UN ratio was considered having increased due to a deficiency in protein and/or amino acids during LP feeding. In Experiment 2, we continuously fed five healthy beagles an LP for 18 weeks and then measured the UCrn/UN ratio as described above. We also measured changes in body composition with computed tomography. At weeks 10 and 18, the fasting UCrn/UN ratio was significantly higher than it was prior to the start of the LP; however, post-prandially, the UCrn/UN ratio decreased to the point that the significant difference disappeared. Muscle mass decreased at weeks 10 and 18. These results suggest that the fasting UCrn/UN ratio could be used as an indicator of protein catabolism in LP feeding. Our experiments thus indicate that examination of potential increases in the UCrn/UN ratio 1 week after introduction of LP feeding to healthy dogs could enable detection of body protein catabolism in long-term feeding of LP before muscle breakdown occurs.